Assessment of the Rural Teacher’s Profile from the Perspective of the Training Process and the Educational Practice - Ramírez-González, Andrea (2015)
This paper presents the results of an evaluation of the profile of rural teachers from the perspective of the teaching practice. The literary sources show different profile approaches that are based on the functions, characteristics, traits, and skills and where the essential aspects of the profile such as skills, abilities, knowledge, attitudes, and values are determined. Consequently, the teaching practice is the ideal context to assess the aspects that shape the rural teacher performance since it allows us to compare the various profile approaches. For the research process, a qualitative methodology was applied, through participant observation techniques and an in-depth interview, to six teachers with university studies in rural education of schools classified as single-teacher and administration 1, located in rural areas of Costa Rica. To retrieve the necessary information to assess the profile of the participants, this research examined the pedagogical-community characteristics of the educational practice, which, at the same time, allow the teacher insertion in alternative work spaces in the rural areas.